2012
DOI: 10.1177/0009922812461069
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring the Morbidity and Mortality Conference in a Department of Pediatrics to Serve as a Vehicle for System Changes

Abstract: The successful change in the focus of the pediatric MMC conference resulted in significant hospital-wide system changes, quality improvements, enhanced education, and departmental satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Recent literature has shown that most healthcare errors are due to system-wide factors, and that individually focused analysis and correction leads to missed opportunities for sustained improvement. 24,25 Nonetheless, the perceived objectives and types of cases selected in the Andean region indicate that M&M conferences are frequently perceived as an opportunity to decide on next steps in an individual patient’s care. While this may be an important function, only a small portion of conferences included elements that were shown to be associated with an effective M&M conference: standardized case selection criteria, documentation of the discussion, and planned follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has shown that most healthcare errors are due to system-wide factors, and that individually focused analysis and correction leads to missed opportunities for sustained improvement. 24,25 Nonetheless, the perceived objectives and types of cases selected in the Andean region indicate that M&M conferences are frequently perceived as an opportunity to decide on next steps in an individual patient’s care. While this may be an important function, only a small portion of conferences included elements that were shown to be associated with an effective M&M conference: standardized case selection criteria, documentation of the discussion, and planned follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…24,24,27 It is worth noting that physical, financial, and human resources were not identified as primary limitations. Business management experts agree that in efforts to implement large-scale culture-changing maneuvers, participants need to experience early “wins”.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In addition, the typical audience at M&M conferences is restricted to the service (mainly physicians or physicians in training) that was involved in the care of the patient, excluding other important members of the multidisciplinary patient care team. 6 To effectively address these shortcomings and to foster an environment focused on patient safety, some institutions have restructured M&M conferences, [7][8][9][10][11][12][13] utilizing an evidence-based systems issues approach, including a broad audience. Using these newer models as a framework, 11,14 the research team initiated a facility-level interdisciplinary improvement conference.…”
mentioning
confidence: 99%
“…When formatted as a nonhierarchical tool inviting contributions from all staff levels, the morbidity and mortality conference plays a key role in the system approach to medical errors. (Pediatr Crit Care Med 2016; 17:67-72) Key Words: adverse events; error and risk analysis; medical error; morbidity and mortality conference; patient safety; pediatric intensive care unit T he morbidity and mortality conference (MMC) served traditionally as an educational aid for medical trainees, but more recently, new emphasis has been placed on patient safety and quality improvement (1)(2)(3)(4)(5)(6)(7)(8), including critical incident monitoring (9), error and risk analysis (10), postincident team debriefings, and the monitoring of quality indicators and adverse events (11). By identifying adverse events and their cause(s), the MMC prompts intervention and may prevent patient harm (8,12,13).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%